Structural and microstructural study of the AlxFe1−x alloy (x=0.25; 0.5 and 0.75) obtained by mechanical grinding - Rocha Cabrera, R (2019)
Alloys Fe-Al in the compositions Al25Fe75, Al50Fe50 and Al75Fe25 were synthesized by the arc furnace technique and the thermally treating 6000C. X-ray diractogram (XRD) and Mössbauer spectroscopy (MS) show the formation of the solid solution Fe(Al) rich and poor in aluminion. Tn the process of mechanical grinding to 10 hours milling maghemite γ − Fe2O3(Al) for compositions Al25Fe75 and Al50Fe50 with aluminiun atoms occupy some iron sites. In the case of the composition Al75Fe25 a single intermetallic Al13Fe4 is observed, remaining structurally invariant for all time nanostructuring.